2017
DOI: 10.1039/c7cc04709f
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3-Promoted hydrogenations of N-heterocycles with ammonia borane

Abstract: A transition-metal-free method for the B(CF)-promoted hydrogenations of N-heterocycles using ammonia borane under mild reaction conditions has been developed. The reaction affords a broad range of hydrogenated products in moderate to good yields. The enantioselective versions for the corresponding products were also investigated via our approach, showing good feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Based on the above observations and previous reports, [14] a plausible reaction mechanism is proposed (Scheme 5). The present reaction proceeds with the generation of a zwitterion species A from B(C 6 F 5 ) 3 and AB.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Based on the above observations and previous reports, [14] a plausible reaction mechanism is proposed (Scheme 5). The present reaction proceeds with the generation of a zwitterion species A from B(C 6 F 5 ) 3 and AB.…”
Section: Resultssupporting
confidence: 53%
“…Varying the amount of BF 3 · OEt 2 did not lead to any improvement (see SI). Attempts to decrease the catalyst loading, the temperature or the amount of AB led to diminished yields of 2 a (Table 1, entries [14][15][16]. Some other boron catalysts, such as (5-bromobenzo[b]thiophen-2yl)boronic acid, [9b] BPh 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates that were deemed electronically symmetric were found to rely on the steric hindrance of the groups that were found to dictate the regiochemistry of the reduction. An additional metal-free method for the BCF-promoted reactivity of heterocycles was reported by Shi and coworkers [40]. They found that BCF was catalytically competent to promote the reduction of various N -heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Representing an area of particular interest, FLPs can be employed as catalysts in metal free hydrogenation processes. [2] Dihydrogen is typically employed as the reductant in such processes,h owever, recent advances have shown that amines, [3] cyclohexadienes, [4] ammonia borane, [5] and Hantzsch esters [6] can be employed as dihydrogen surrogates in B(C 6 F 5 ) 3 -catalyzed transfer hydrogenation. Systems employing an additional Lewis base,r endering it an FLPtype process,have been developed by Du and co-workers for the enantioselective transfer hydrogenation of ketimines and quinoxalines.…”
mentioning
confidence: 99%